2014
DOI: 10.3892/mmr.2014.2603
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gastrokine-2 expression on gastric cancer cell apoptosis by activation of extrinsic apoptotic pathways

Abstract: Gastrokine-2 is a putative gastric cancer-specific tumor suppressor gene, the loss of which is known to be involved in the development and progression of gastric cancer, and restoration of gastrokine-2 expression inhibits growth of gastric cancer cells in vitro. However, the underlying mechanism of these effects requires elucidation. In the present study, expression patterns of gastrokine-2 protein were examined in gastric cancer tissues and cell lines. Expression of gastrokine-2 was restored in gastric cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Furthermore, a previous study reported that Fas facilitates the caspase-8 dimerization and maturation process (30). The present study demonstrated that Fas expression was correlated with caspase-8 expression and this was consistent with previously reported data (2830). …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, a previous study reported that Fas facilitates the caspase-8 dimerization and maturation process (30). The present study demonstrated that Fas expression was correlated with caspase-8 expression and this was consistent with previously reported data (2830). …”
Section: Discussionsupporting
confidence: 94%
“…The present study demonstrated that the caspase-8 expression was lower in gastric cancer tissues compared with healthy gastric tissues and was correlated with Fas expression in gastric cancer tissues and cell lines. Previous studies revealed that functional grade purified Fas activated caspase 8 in extrinsic apoptosis, and recruited procaspase-8 to form DISC in extrinsic apoptosis in gastric cancer cells (28,29). Furthermore, a previous study reported that Fas facilitates the caspase-8 dimerization and maturation process (30).…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al have demonstrated that GKN2 may induce apoptosis by activating Fas, caspase-3, and caspase-8 [33]. In this study, ectopic TFF1 expression was linked to a considerably elevated percentage of apoptotic cells compared to a mock control (Fig.…”
Section: Discussionmentioning
confidence: 50%
“…The efficacy of chemotherapy drugs can be evaluated by their ability to induce apoptosis. The upregulation of caspase-3 and the reduction of mitochondrial membrane potential may result in apoptosis, so an ideal chemotherapy drug would cause these alterations (16,17).…”
Section: Introductionmentioning
confidence: 99%